Navigating uncertainty and competing objectives: Spring chinook salmon recovery in the upper Willamette river - Claire E. Couch; J. Rose Wallick; James T. Peterson; Bailey A. Morgan; Matthew L. Keefer; Christopher C. Caudill; Kathleen G. O’Malley; Christina A. Murphy; James S. White; Jake R. Kelley; Dalton J. Hance; Gabriel S. Hansen; et al. (Reviews in Fish Biology and Fisheries, 2026)

Advancing Ecological Understanding and Sustainable Management of Small Pelagic Fish - Myron A. Peck; Ignacio A. Catalán; Ryan R. Rykaczewski; Akinori Takasuka; Susana Garrido; Rebecca G. Asch; Matthew R. Baker; Noelle M. Bowlin; Jennifer Boldt; Richard D. Brodeur; Cecilie Hansen; Salvador E. Lluch‐Cota; et al. (Fish and Fisheries, 2026)
Small pelagic fish (SPF) are critical to the trophodynamic structure and function of marine systems and support some of the most valuable and socially important fisheries worldwide. Their “boom and bust” population dynamics, shifts in distribution, and importance as forage resources for other fish stocks place unique challenges to assessing and managing SPF. In response to these challenges, an international working group was formed in 2019 to foster collaboration aimed at closing key knowledge gaps in the ecology and sustainable management of SPF. Here, that group reviews progress made over the last ~10 years and identifies priorities for the next stage of coordinated international collaboration. Key research needs include: (i) enhancing monitoring programs to capture shifts in SPF distribution and incorporating new technologies, from molecular tools and digital imaging to biophysical and ecological modelling, (ii) improving data sharing to better understand life‐history bottlenecks and cross‐regional population dynamics, (iii) advancing process‐based studies on oceanic and trophodynamic interactions to clarify the ecological roles of SPF as both predators and prey, and (iv) conducting bioeconomic and risk analyses to assess the vulnerability of fishing‐dependent human communities to environmental and fish population fluctuations. A key pathway forward involves integrating mechanistic ecological knowledge, ecosystem and bioeconomic modelling, and social‐ecological frameworks into real‐time, adaptive, and equitable management approaches. This integration will be essential for developing resilient, ecosystem‐based fisheries management capable of anticipating tipping points, accommodating non‐stationary population dynamics, and ensuring sustainability under future climate and socio‐economic uncertainties.

Structure elucidation of leadbeaterin-1, an ichthyotoxin associated with fish-killing blooms of Chrysochromulina leadbeateri in Northern Norwegian fjords - Xinhui Wang; Anita Solhaug; Bruno C. Garrido; Elizabeth M. Mudge; Mathias Fon; Aaron J.C. Andersen; Ingunn A. Samdal; Bente Edvardsen; Charlotte H. Gotfredsen; Per Juel Hansen; Christopher O. Miles; Thomas O. Larsen (Harmful Algae, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Bright spots for advancing ecological understanding and conservation decision‐making - Holly S. Embke; Zachary S. Feiner; Gretchen J. A. Hansen; Daniel Isermann; Olaf P. Jensen; Christopher I. Rounds; Quinnlan C. Smith; M. Jake Vander Zanden (Conservation Biology, 2025)
A lot can be learned by studying bright spots—defined as unexpected positive outcomes. In fields like public health, education, and oncology, identifying factors behind bright spots reveals previously unknown drivers of success that can be replicated elsewhere. This concept is being applied in conservation but is hampered by variations in definitions of bright spots and confusion with hotspots—sites with high absolute values of a metric. We developed a framework to clearly define and distinguish between hotspots (e.g., a wetland with high plant diversity) and bright spots (e.g., a biodiverse wetland in a housing development), which outperform conservation expectations. The framework is an iterative cycle, consisting of setting expectations for relative comparisons, classifying systems into bright, dark, hot, and cold categories, and digging deeper to reveal hidden mechanisms and opportunities for intervention. We drew on examples from diverse fields to demonstrate how our framework can generate new knowledge, identify potential interventions, and inform management priorities. Defining conservation and management expectations, often through predictive models, is essential to understanding drivers of success and fosters hypotheses about overlooked factors. Our framework can enhance ecological understanding, guide interventions, and help prioritize actions in conservation and natural resource management.

Healing Ogaa (Walleye Sander vitreus ) Waters: Lessons and Future Directions for Inland Fisheries Rehabilitation - Holly S. Embke; Zachary S. Feiner; Gretchen J. A. Hansen; Joseph T. Mrnak; Michael Waasegiizhig Price; Christopher Rounds; Greg G. Sass; Stephanie L. Shaw; Aaron Shultz (Reviews in Fisheries Science & Aquaculture, 2025)

ThinCurr: An open-source 3D thin-wall eddy current modeling code for the analysis of large-scale systems of conducting structures - Christopher Hansen; Alexander Battey; Anson Braun; Sander Miller; Michael Lagieski; Ian Stewart; Ryan Sweeney; Carlos Paz-Soldan (Computer Physics Communications, 2025)

Stacking and Intersecting Nitrogen 4Rs on Potato: Economic Analysis - Samuel H. Stapley; Christopher S. McIntosh; Matt A. Yost; Neil C. Hansen; Ryan C. Christensen; Bryan G. Hopkins (American Journal of Potato Research, 2025)
The 4Rs of nutrient management is an initiative to balance economics with sustainability. The objective was to evaluate individual and stacked 4R practices on potato ( Solanum tuberosum L.) profitability. Treatments included all combinations of two nitrogen (N) sources (urea or polymer coated urea [PCU]), two rates (82 or 100%), and/or two timing/placements (at emergence or split-applied). Gross income and net profit were determined using yields, market sale data, and costs. Total gross income was greatest for PCU split applied and PCU at emergence in 2020 and 2023, respectively. Gross income and net profit were higher for the full rate for PCU compared to urea. The detrimental effect of the reduced rate disappeared with PCU, but not urea. A reduced rate of PCU was similar to a full rate of split applied urea. These data suggest that PCU is a profitable N source for potato even at reduced rates.

Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núnez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2025)

Corrigendum to “long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum” [science of the total environment, 908 (2024)/ 168,042] - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núñez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2025)

Climate‐driven alterations of lake thermal regimes - Christopher J. Sullivan; Jordan S. Read; Gretchen J. A. Hansen (Limnology and Oceanography, 2025)
Temperate lakes are undergoing climate‐driven alterations in their thermal regimes, changing their ecology. Previous efforts to understand temperature changes have overlooked multi‐dimensional temperature dynamics, missing complex shifts at high spatiotemporal resolutions across landscapes. Here, we use simulated daily water temperature profiles from > 11,000 temperate lakes throughout the Midwestern United States to (1) quantify multivariate, landscape‐scale patterns in contemporary thermal regimes and (2) contextualize forecasted shifts and identify novel regimes that may emerge with climatic change. Hierarchical clustering and principal component analyses identified six lake clusters with distinct thermal regimes driven by differences in annual warming rates and spring–summer dynamics, with secondary influences from extreme heat events and seasonal variability. Annual temperature variations were influenced by lake‐specific physical characteristics, emphasizing distinct thermal profiles and seasonal variability patterns. Projected climate‐driven alterations in thermal regimes suggest a homogenization toward warmer and more variable conditions, with the majority of lakes characterized by higher temperatures and increased variability. Few lakes ( n = 310), particularly in the southern and southeastern Midwest, may experience novel, non‐analog conditions by the late 21 st century, while others will undergo shifts between clusters but remain within analogous regime frameworks. Projected changes in lake thermal regimes highlight concerns about ecological impacts on aquatic species and habitats, especially as extreme and variable growing season temperatures intensify and periods of stratification become prolonged. Furthermore, we identify thermal regimes that are likely to dominate the region by the late 21 st century while identifying those likely to be lost. The ecological consequences of such changes remain unknown.

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Metabolism diversification of ammonia-oxidizing archaea and bacteria under different precipitation gradients and land legacies - Soumyadev Sarkar; Anna Kazarina; Paige M. Hansen; Kaitlyn Ward; Christopher Hargreaves; Nicholas Reese; Qinghong Ran; Willow Kessler; Ligia F.T. de Souza; Terry D. Loecke; Marcos V.M. Sarto; Charles W. Rice; et al. (Applied Soil Ecology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A framework for national-scale coastal storm hazards early warning - Ian L. Turner; Christopher K. Leaman; Mitchell D. Harley; Mandi C. Thran; Daniel R. David; Kristen D. Splinter; Nashwan Matheen; Jeff E. Hansen; Michael V.W. Cuttler; Diana J.M. Greenslade; Stefan Zieger; Ryan J. Lowe (Coastal Engineering, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Predicting responses to climate change using a joint species, spatially dependent physiologically guided abundance model - Christopher A. Custer; Joshua S. North; Erin M. Schliep; Michael R. Verhoeven; Gretchen J. A. Hansen; Tyler Wagner (Ecology, 2024)
Predicting the effects of warming temperatures on the abundance and distribution of organisms under future climate scenarios often requires extrapolating species–environment correlations to climatic conditions not currently experienced by a species, which can result in unrealistic predictions. For poikilotherms, incorporating species' thermal physiology to inform extrapolations under novel thermal conditions can result in more realistic predictions. Furthermore, models that incorporate species and spatial dependencies may improve predictions by capturing correlations present in ecological data that are not accounted for by predictor variables. Here, we present a joint species, spatially dependent physiologically guided abundance (jsPGA) model for predicting multispecies responses to climate warming. The jsPGA model uses a basis function approach to capture both species and spatial dependencies. We apply the jsPGA model to predict the response of eight fish species to projected climate warming in thousands of lakes in Minnesota, USA. By the end of the century, the cold‐adapted species was predicted to have high probabilities of extirpation across its current range—with 10% of lakes currently inhabited by this species having an extirpation probability >0.90. The remaining species had varying levels of predicted changes in abundance, reflecting differences in their thermal physiology. Though the model did not identify many strong species dependencies, the variation in estimated spatial dependence across species suggested that accounting for both dependencies was important for predicting the abundance of these fishes. The jsPGA model provides a new tool for predicting changes in the abundance, distribution, and extirpation probability of poikilotherms under novel thermal conditions.

Experimental modification of African wild dog movement and behavior using translocated conspecific scent - K. Whitney Hansen; Neil R. Jordan; Megan J. Claase; Justin P. Suraci; John W. McNutt; Aanya Dhruv; Christopher C. Wilmers (Biological Conservation, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Long-read genome sequencing provides novel insights into the harmful algal bloom species Prymnesium parvum - Jianbo Jian; Zhangyan Wu; Arisbe Silva-Núñez; Xiaohui Li; Xiaomin Zheng; Bei Luo; Yun Liu; Xiaodong Fang; Christopher T. Workman; Thomas Ostenfeld Larsen; Per Juel Hansen; Eva C. Sonnenschein (Science of The Total Environment, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Lymphatic cells do not functionally integrate into 3D organotypic brain slice cultures, but aggregate around penetrating blood vessels - Cornelius H. Lam; Christopher Janson; Liudmila Romanova; Eric A. Hansen (Experimental Brain Research, 2022)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Electronic monitoring in fisheries: Lessons from global experiences and future opportunities - Aloysius T.M. van Helmond; Lars O. Mortensen; Kristian S. Plet‐Hansen; Clara Ulrich; Coby L. Needle; Daniel Oesterwind; Lotte Kindt‐Larsen; Thomas Catchpole; Stephen Mangi; Christopher Zimmermann; Hans Jakob Olesen; Nick Bailey; et al. (Fish and Fisheries, 2020)
Since the beginning of the 21st century, electronic monitoring (EM) has emerged as a cost‐efficient supplement to existing catch monitoring programmes in fisheries. An EM system consists of various activity sensors and cameras positioned on vessels to remotely record fishing activity and catches. The first objective of this review was to describe the state of play of EM in fisheries worldwide and to present the insights gained on this technology based on 100 EM trials and 12 fully implemented programmes. Despite its advantages, and its global use for monitoring, progresses in implementation in some important fishing regions are slow. Within this context, the second objective was to discuss more specifically the European experiences gained through 16 trials. Findings show that the three major benefits of EM were as follows: (a) cost‐efficiency, (b) the potential to provide more representative coverage of the fleet than any observer programme and (c) the enhanced registration of fishing activity and location. Electronic monitoring can incentivize better compliance and discard reduction, but the fishing managers and industry are often reluctant to its uptake. Improved understanding of the fisher's concerns, for example intrusion of privacy, liability and costs, and better exploration of EM benefits, for example increased traceability, sustainability claims and market access, may enhance implementation on a larger scale. In conclusion, EM as a monitoring tool embodies various solid strengths that are not diminished by its weaknesses. Electronic monitoring has the opportunity to be a powerful tool in the future monitoring of fisheries, particularly when integrated within existing monitoring programmes.

Weddell-Scotia Confluence Effect on the Iron Distribution in Waters Surrounding the South Shetland (Antarctic Peninsula) and South Orkney (Scotia Sea) Islands During the Austral Summer in 2007 and 2008 - Nicolas Sanchez; Christian S. Reiss; Osmund Holm-Hansen; Christopher D. Hewes; Kemal C. Bizsel; Murat V. Ardelan (Frontiers in Marine Science, 2019)

Passive acoustic monitoring predicts daily variation in North Atlantic right whale presence and relative abundance in Roseway Basin, Canada - Delphine Durette‐Morin; Kimberley T. A. Davies; Hansen D. Johnson; Moira W. Brown; Hilary Moors‐Murphy; Bruce Martin; Christopher T. Taggart (Marine Mammal Science, 2019)
North Atlantic right whale monitoring in Roseway Basin, Canada, is primarily based on short‐term ( n = 23 d) implied a 40% decline in right whale presence during 2014–2015 relative to 2004–2005, PAM data ( n = 211 d) showed right whales were present between 71%–85% of survey days throughout all years analyzed. We demonstrate that PAM is a useful tool to extend periods of right whale monitoring, especially in areas where visual monitoring efforts may be limited.

Viator vitreocola gen. et sp. nov. (Stylonematophyceae), a new red alga on drift glass debris in Oregon and Washington, USA - Gayle I. Hansen; John A. West; Hwan Su Yoon; Christopher D. Goodman; Susan Loiseaux-de Goër; Giuseppe C. Zuccarello (Algae, 2019)

The effects of blood and blood products on the arachnoid cell - Eric A. Hansen; Liudmila Romanova; Christopher Janson; Cornelius H. Lam (Experimental Brain Research, 2017)

Addition of 20-kDa PEG to Insulin Lispro Alters Absorption and Decreases Clearance in Animals - Mary Pat Knadler; Tri-Hung Nguyen; Kristina Campanale; Michael J. De Veer; John M. Beals; Shun Li; Ryan Hansen; Angela Siesky; M. Dodson Michael; Christopher J. H. Porter (Pharmaceutical Research, 2016)

Song sharing and diversity in the Bering‐Chukchi‐Beaufort population of bowhead whales ( Balaena mysticetus ), spring 2011 - Hansen D. Johnson; Kathleen M. Stafford; J. Craig George; William G. Ambrose; Christopher W. Clark (Marine Mammal Science, 2015)
Bowhead whales ( Balaena mysticetus ) of the Bering‐Chukchi‐Beaufort population migrate in nearshore leads through the Chukchi Sea each spring to summering grounds in the Beaufort Sea. As part of a population abundance study, hydrophones were deployed in the Chukchi Sea off Point Barrow, (12 April to 27 May 2011) and in the Beaufort Sea (12 April to 30 June 2011). Data from these sites were analyzed for the presence of bowhead whale song. We identified 12 unique song types sung by at least 32 individuals during ~95 h of recordings off Point Barrow. Six of these songs were detected at the Beaufort MARU site as well as six additional song types that were not analyzed. These results suggest a shared song repertoire among some individuals. This report represents the greatest number of songs to date during the spring migration for this population. We attribute this greater variety to population growth over the 30 yr since acoustic monitoring began in the early 1980s. Singing during early to mid‐spring is consistent with the hypothesis that song is a reproductive display, but further research is necessary to understand the exact function of this complex vocal behavior.

Analysis and Validation of Putative Substances Involved in Fatal Poisonings - Christopher K. Hansen; John Kashani; Bruce Ruck; Steven Marcus (Journal of Medical Toxicology, 2012)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

Quantitative trait loci analysis for resistance to Cephalosporium stripe, a vascular wilt disease of wheat - Martin C. Quincke; C. James Peterson; Robert S. Zemetra; Jennifer L. Hansen; Jianli Chen; Oscar Riera-Lizarazu; Christopher C. Mundt (Theoretical and Applied Genetics, 2011)

Early adaptive developments of Pseudomonas aeruginosa after the transition from life in the environment to persistent colonization in the airways of human cystic fibrosis hosts - Martin Holm Rau; Susse Kirkelund Hansen; Helle Krogh Johansen; Line Elnif Thomsen; Christopher T. Workman; Kristian Fog Nielsen; Lars Jelsbak; Niels Høiby; Lei Yang; Søren Molin (Environmental Microbiology, 2010)
Summary Pseudomonas aeruginosa is an opportunistic pathogen ubiquitous to the natural environment but with the capability of moving to the host environment. Long‐term infection of the airways of cystic fibrosis patients is associated with extensive genetic adaptation of P. aeruginosa , and we have studied cases of the initial stages of infection in order to characterize the early adaptive processes in the colonizing bacteria. A combination of global gene expression analysis and phenotypic characterization of longitudinal isolates from cystic fibrosis patients revealed well‐known characteristics such as conversion to a mucoid phenotype by mucA mutation and increased antibiotic resistance by nfxB mutation. Additionally, upregulation of the atu operon leading to enhanced growth on leucine provides a possible example of metabolic optimization. A detailed investigation of the mucoid phenotype uncovered profound pleiotropic effects on gene expression including reduction of virulence factors and the Rhl quorum sensing system. Accordingly, mucoid isolates displayed a general reduction of virulence in the Caenorhabditis elegans infection model, altogether suggesting that the adaptive success of the mucoid variant extends beyond the benefits of alginate overproduction. In the overall perspective the global phenotype of the adapted variants appears to place them on paths in direction of fully adapted strains residing in long‐term chronically infected patients.

US Forest Service Bark Beetle Research in the Western United States: Looking Toward the Future - José F. Negròn; Barbara J. Bentz; Christopher J. Fettig; Nancy Gillette; E. Matthew Hansen; Jane L. Hayes; Rick G. Kelsey; John E. Lundquist; Ann M. Lynch; Robert A. Progar; Steven J. Seybold (Journal of Forestry, 2008)
Bark beetles cause extensive tree mortality in coniferous forests of western North America and play an important role in the disturbance ecology of these ecosystems. Recently, elevated populations of bark beetles have been observed in all conifer forest types across the western United States. This has heightened public awareness of the issue and triggered legislation for increased funding for state and federal agencies to address issues associated with bark beetle outbreaks. Recently, US Forest Service, Research and Development entomologists from the western research stations met with US Forest Service, State and Private Forestry, Forest Health Protection entomologists, our primary stakeholder, to identify bark beetle research priorities. These include vegetation management; ecological, economic, and social consequences of outbreaks; fire and bark beetle interactions; effects of climate change on bark beetle populations; and chemical ecology.

Potential impacts of global climate change on freshwater fisheries - Ashley D. Ficke; Christopher A. Myrick; Lara J. Hansen (Reviews in Fish Biology and Fisheries, 2007)

Iron limitation across chlorophyll gradients in the southern Drake Passage: Phytoplankton responses to iron addition and photosynthetic indicators of iron stress - Brian M. Hopkinson; B. Greg Mitchell; Rick A. Reynolds; Haili Wang; Karen E. Selph; Christopher I. Measures; Christopher D. Hewes; Osmund Holm-Hansen; Katherine A. Barbeau (Limnology and Oceanography, 2007)
Processes influencing phytoplankton bloom development in the southern Drake Passage were studied using shipboard iron‐enrichment incubations conducted across a surface chlorophyll gradient near the Antarctic Peninsula, in a region of water mass mixing. Iron incubation assays showed that Antarctic Circumpolar Current (ACC) waters were severely iron limited, while shelf waters with high ambient iron concentrations (1–2 nmol L −1 ) were iron replete, demonstrating that mixing of the two water masses is a plausible mechanism for generation of the high phytoplankton biomass observed downstream of the Antarctic Peninsula. In downstream highchlorophyll mixed waters, phytoplankton growth rates were also iron limited, although responses to iron addition were generally more moderate as compared to ACC waters. Synthesizing results from all experiments, significant correlations were found between the initial measurements of Photosystem II (PSII) parameters ( F v :F m , σ PSII , and p ) and the subsequent responses of these waters to iron addition. These correlations indicate that PSII parameters can be used to assess the degree of iron stress experienced in these waters and likely in other regions where photoinhibition and nitrogen stress are not confounding factors.

Innovativeness in the North American Softwood Sawmilling Industry - Pablo Crespell; Christopher Knowles; Eric Hansen (Forest Science, 2006)
The North American forest products industry has traditionally maintained a production orientation and a commodity mentality toward operations, with much of the industry following a low-cost strategy and concentrating on wood fiber recovery. The propensity to innovate (innovativeness) is important for maintaining firm competitiveness. To assess industry practices with respect to innovativeness, United States and Canadian softwood sawmills were surveyed. Respondents rated themselves more innovative with respect to manufacturing processes as compared to product and business systems innovations. Innovativeness and market orientation were found to be positively correlated. High- and medium-innovative mills were consistently different (e.g., more market-oriented, more structured new product development processes) from low-innovative mills.

Deep chlorophyll-a maxima (DCMs) in Antarctic waters - Osmund Holm-Hansen; Christopher D. Hewes (Polar Biology, 2004)

Reliable short-term memory in the trion model: toward a cortical language and grammar - Milind Sardesai; Christopher Figge; Mark Bodner; Meridith Crosby; Jill Hansen; Jorge A. Quillfeldt; Susan Landau; Annette Ostling; Sydni Vuong; Gordon L. Shaw (Biological Cybernetics, 2001)

Sensory irritation mechanisms investigated from model compounds: trifluoroethanol, hexafluoroisopropanol and methyl hexafluoroisopropyl ether - G. D. Nielsen; Michael H. Abraham; Lea F. Hansen; Maria Hammer; Christopher J. Cooksey; Jenik Andonian-Haftvan; Yves Alarie (Archives of Toxicology, 1996)